Performance of Relocation Policy Implementation at Purbalingga Food Center - Karina Nuur Annisa; Slamet Rosyadi; Lilis Sri Sulistiani (Jurnal Public Policy, 2022)
The relocation policy is a government action in an effort to reposition street vendors from one place to another, which is considered more appropriate for several reasons and purposes. The purpose of this study is to find out how the performance of the relocation policy at the Purbalingga Food Center is based on aspects of communication, access, coverage, accountability, and program adjustment to needs. The results of this study explain that the performance of the implementation of this relocation policy when viewed based on aspects of communication, access to accountability, and program adjustments to needs that have been running well, but not optimal. This happens because there is no adjustment to the type of trade with the facilities provided and there is a lack of adequate facilities. To be able to improve the performance of the implementation of this relocation policy, the policy organizers must provide training and guidance to the actors at the Purbalingga Food Center consistently and sustainably, as well as maintain and improve all aspects, namely communication, access, accountability, and program suitability, that have been going well, in order to achieve maximum policy objectives.